Determining the degree of effect of heat flows on the deformation of the shell of a space inflatable platform with a payload - Lapkhanov, Erik; Palii, Oleksandr; Golubek, Aleksandr (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports a study into the influence exerted by the thermal flows of space environment on the deformation of the shell of a space inflatable platform with a payload. The mathematical model of the effect of temperature fluctuations on the mass-inertial characteristics of the space inflatable platform of an ellipsoidal shape has been improved. The following assumptions were introduced to the model. The temperature distribution on the illuminated part and the unlit part of the shell is uniform. The gradient of the temperature difference between the illuminated and unlit parts is the same for all points of the shell. To determine deformations, a moment-free theory was used. The model of the space inflatable platform is a «rubber bullet» that works only for stretching and compression. All deformations are elastic. The advantages and limitations of the use of the developed mathematical model have been determined. Computer simulation of the orbital motion of a space inflatable platform with a payload in a sun-synchronous orbit was carried out. The material of the platform shell is Kapton. Estimates of temperature fluctuations in the illuminated and unlit part of the shell and the temperature of the gas inside it were obtained. The dependence of elastic deformations on temperature was determined, taking into account the Young’s modulus of the material. The influence of changes in gas pressure on the movement of payload attachment points and the change in the inertia tensor have been determined. The obtained results showed that the inertia tensor varies within the order of 10–5 kgm2. The maximum deviation of the fastening points of the payload from the initial position on the illuminated part of the shell was about 10–6 m. Considering the stability of the structure to the effects of heat flows of the space environment, the possibility of using space inflatable platforms as a means for separating a grouping of satellites has been shown